PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF PORTULACA QUADRIFIDA LINN. - SUPRIYA, JAGTAP; KISHOR, GUJAR; ANIKET, GHARE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate in vitro antimicrobial activity against enterotoxigenic Escherichia coli and Bacillus subtilis and preliminary phytochemical screening of the leaves of Portulaca quadrifida (Linn.). Methods: The solvent extract such as petroleum ether, methanol, and water on the leaves of P. quadrifida (Linn) was prepared by Soxhlet extraction (continuous hot percolation method). These solvent extracts were screened for antimicrobial activity against enterotoxigenic E. coli and B. subtilis at various concentrations and were measured by observing zone of inhibition in mm by disc diffusion method (cup plate method). Results: The preliminary phytochemical screening revealed the flavonoids, fats, and oils in all extracts. Similarly, the presence of alkaloids and tannins was obtained in the petroleum ether and methanolic extracts, while the presence of glycosides was obtained in the methanolic and water extracts. Further, proteins and sterols were found in petroleum extracts. The results of antimicrobial activity shown that methanolic extracts of the plant leaf showed good antimicrobial activity and petroleum ether and water extract showed similar activity but less antimicrobial activity than methanolic extract. The antimicrobial activities of extracts were compared with standard antibiotic such as chloramphenicol. Conclusion: P. quadrifida (Linn.) has broad-spectrum antimicrobial activity and a potential source of new classes of antibiotics that could be useful for infectious disease chemotherapy and control. The phytochemical analysis of the crude extracts of this plant indicates the presence of major phytoconstituents which may have been responsible for the observed antimicrobial property.